(untitled) (Revista Ciência Agronômica, 2023)
The aim of this study was to develop bell pepper hybrids with resistance to multiple pathogens and make inferences in regard to components of heterosis in hybrids obtained from lines presumed to be resistant to Pepper yellow mosaic virus (PepYMV), Phytophthora capsici, or Meloidogyne incognita. The studies were carried out in a greenhouse. We used ten lines, thirty experimental hybrids, and seven controls (Konan-R, Magali-R, Martha-R, Stephany, Mallorca, Magnata Super, and Criollo de Morelos-334). For all experiments, a randomized block design was used with three replications (with plots composed of 16 plants). For evaluation of the reactions to P. capsici and to PepYMV, the percentages of asymptomatic plants were considered. For evaluation of the reactions to M. incognita, the reproduction index and the reproduction factor of the nematode were calculated. The additive gene effects were important for all the traits evaluated, and for percentage of plants resistant to PepYMV and P. capsici, the non-additive effects were also important. The alleles that control resistance to PepYMV, to P. capsici, and to M. incognita have a degree of dominance near 1, in absolute value, which indicates a favorable situation for obtaining hybrids that accumulate multiple resistance to these pathogens.